The validity of self-reported number of teeth and edentulousness among Norwegian older adults, the HUNT Study - Hedda Høvik; Marit Kolberg; Linda Gjøra; Line Cathrine Nymoen; Rasa Skudutyte-Rysstad; Lene Hystad Hove; Yi-Qian Sun; Tone Natland Fagerhaug (BMC, 2022)
Abstract Background Number of teeth is an established indicator of oral health and is commonly self-reported in epidemiological studies due to the costly and labor-intensive nature of clinical examinations. Although previous studies have found self-reported number of teeth to be a reasonably accurate measure, its accuracy among older adults ≥ 70 years is less explored. The aim of this study was to assess the validity of self-reported number of teeth and edentulousness in older adults and to investigate factors that may affect the accuracy of self-reports. Methods This study included two different samples of older adults ≥ 70 years drawn from the fourth wave of the Trøndelag Health Study (the HUNT Study), Norway. Sample 1 (n = 586) was used to evaluate the validity of self-reported number of teeth and sample 2 (n = 518) was used to evaluate self-reported edentulousness. Information on number of teeth and background variables (education, smoking, cognitive function, and self-perceived general and oral health) were self-reported in questionnaires, while clinical oral health examinations assessed number of teeth, number of teeth restored or replaced by fixed prosthodontics and edentulousness. Spearman and Pearson correlation coefficients, Bland-Altman plot, chi-square test and kappa statistics were used to assess the agreement between self-reported and clinically recorded number of teeth. Results The mean difference between self-reported and clinically recorded number of teeth was low (− 0.22 teeth), and more than 70% of the participants reported their number of teeth within an error of two teeth. Correlations between self-reports and clinical examinations were high for the total sample (0.86 (Spearman) and 0.91 (Pearson)). However, a lower correlation was found among participants with dementia (0.74 (Spearman) and 0.85 (Pearson)), participants having ≥ 20 teeth (0.76 (Spearman) and 0.67 (Pearson)), and participants with ≥ 5 teeth restored or replaced by fixed prosthodontics (0.75 (Spearman) and 0.77 (Pearson)). Self-reports of having teeth or being edentulous were correct in 96.3% of the cases (kappa value 0.93, p value < 0.001). Conclusions Among older Norwegian adults, self-reported number of teeth agreed closely with clinical tooth counts and nearly all the edentulous participants correctly reported having no teeth.